Exploring the challenges for a new classification of adenomyosis. Issue 4 (April 2020) - Habiba, Marwan; Gordts, Stephan; Bazot, Marc; Brosens, Ivo; Benagiano, Giuseppe
Abstract: The availability of non-invasive diagnostic tests is an important factor in the renewed interest in adenomyosis, as the disease can now be more accurately mapped in the uterus without a need for hysterectomy. An agreed system for classifying and reporting the condition will enhance our understanding of the disease and is envisaged to enable comparison of research studies and treatment outcomes. In this review, we assess previous and more recent attempts at producing a taxonomy, especially in view of the latest proposal for subdivision of adenomyosis into an internal and an external variant. In this context, we also explore the uncertainties linked to classifying involvement of the uterovesical pouch, the pouch of Douglas and lesions in the outer myometrium. Two opposing hypotheses are forwarded to explain the pathogenesis of these variants, namely that disease localized in these areas originates from an invasion by uterine adenomyosis of peritoneal organs; alternatively, that lesions present in the outer myometrium originate from peritoneal endometriosis. At the root of debates around these opposing theories of pathogenesis is fragmentary evidence. Because of the limitations of currently available evidence, and until this issue is resolved, broad agreement on a hypothesis to underpin any proposed classification is unlikely.